Generating switchable and reconfigurable optical vortices via photopatterning of liquid crystals - Wei, Bing-yan (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.